Comparison between cone beam computed tomography and panoramic radiography in the assessment of the relationship between the mandibular canal and impacted class C mandibular third molars - Zahra Dalili; Porousha Mahjoub; Ali Khalighi Sigaroudi (Wolters Kluwer Medknow Publications, 2011)
Background: Preoperative radiographic evaluation of impacted third molars is essential to determine the proximity to the mandibular canal to minimize the risk of nerve injury. Our study aim was to evaluate the relationship between the mandibular canal and impacted mandibular third molars using cone beam computed tomography (CBCT) and to compare findings therein with panoramic radiographic signs. Methods: CBCT images were taken from 29 patients having 43 Class C impacted mandibular third molars whose panoramic radiographs showed a close relationship between the mandibular canal and mandibular third molars. We evaluated their tomographs to determine the course of the canal, its proximity to the root, any narrowing of the canal, the presence of root grooving or hooks and the proximity of the root to the cortex. A Chi-square test was used for data analysis. Results: The lingual course of the canal was the most frequently detected course in all panoramic findings. Contact of the tooth with the canal was observed in all cases in which panoramic signs of deviation of the canal and darkening of the roots were found. The frequency of observing the narrowing of the canal in CBCT as compared to seeing the presence or the absence of canal narrowing in panoramic radiographs was significantly different (P=0.01). Conclusion: CBCT provides more precise diagnostic information to determine the relationship of impacted third molars to the canal. Deviation of the canal and darkening of the roots in panoramic view can be highly valuable to predict the risk of nerve injury.